Lycophytes and monilophytes of the Bosque Rodrigues Alves Jardim Botânico da Amazônia, municipality of Belém, Pará State, Brazil - Maciel, Sebastião; Souza, Maria Goreti Coelho de; Pietrobom, Marcio Roberto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
This study deals with an inventory of the Lycophytes and Monolophytes of the Bosque Rodrigues Alves Jardim Botânico da Amazônia (BRAJBA), as part of a study series of the Lycophytes and Monolophytes (Pteridophyta) from ecosystems of Pará. The studied area is situated in the metropolitan region of Belém and is a fragment of 15 ha of non-inundated rain forest. As a contribution to the knowledge of the pteridophyte flora of Pará, seven collection trips were made, resulting in the registration of 14 families, 27 genera and 39 species. The best represented families were Pteridaceae with 10 species, Hymenophyllaceae with 6 species and Polypodiaceae with 5 species. Four species were newly recorded in northern Brazil (Adiantum tenerum Sw., Dennstaedtia cicutaria (Sw.) T. Moore, Salvinia minima Baker and Selaginella willdenowii (Desv. Ex Poir.) Baker). The majority (27) of the species has neotropical distribution, but Asplenium angustum Sw. and Trichomanes pinnatinervium Jenman are restricted to northern South America and to the Brazilian Amazonia.